Impact of green finance on poverty reduction: evidence from China - Wei Xu; Xiaoning Wang; Yun Zhang; Feng Wang (Environmental Research Communications)
Integrating environmental sustainability within the financial sector, known as green finance, offers a promising approach to poverty reduction in China. This study investigates the impact of green finance on poverty reduction in China. We construct a comprehensive index of green finance, which includes green credit, green insurance, and green investment, to evaluate its development across China’s provinces. We uncover the intricate relationship between green finance and poverty reduction using panel data regression analysis on a dataset spanning 30 provinces from 2010 to 2021. Our findings indicate a positive and significant association between the advancement of green finance and poverty reduction. Notably, this effect is most pronounced in Eastern China, intermediate in Central China, and the least in Western China. This regional disparity underscores the need for geographically sensitive policy interventions to harness green finance’s poverty-reducing potential effectively. Furthermore, we identify economic growth and industrial structure upgrading as primary mediators between green finance and poverty reduction. While environmental improvement plays a role, its impact as a mediator is relatively small, suggesting a more nuanced approach to integrating environmental sustainability with poverty reduction strategies. The study contributes to the literature by providing empirical evidence on the effectiveness of green finance in poverty reduction. It offers insights for policymakers to enhance green finance strategies, emphasizing economic growth, industrial advancement, and sustainable development.